The Influence of Governance on Competence and Partnership in Higher Education: A Study of Gambian Universities - Badjie, Gibriel; Jammeh, Lamin B; Sawaneh, Banna; Sanyang, Lang (Jurnal Ilmiah Aset, 2024)
The study assesses the influence of governance on competence and partnership in university education in The Gambia using the situation as a mediating factor in a trilateral relationship. The study applied a questionnaire survey design using three universities as the study population. The PLS-SEM approach assesses the measurements and structural models. The study's findings established that governance significantly influences competence and partnership in university education in The Gambia. However, the situation as an environmental factor lacks the mediation capacity in the trilateral relationship. The study outcome shows differences, but only two were significantly contextual in relation to governance. The study recommends further research that adopts a qualitative approach to help provide a proper understanding of university governance in The Gambia.